The Spatial Distribution of Tree Dieback Affected by Mistletoe in Relation to their Crown Characteristics - Erfan Boshkar; Ehsan Sayad; Shayeste Gholami (جغرافیا و پایداری محیط)
1- Introduction One of the main problems in The Zagros Forests is oak trees dieback. What is really certain and important is the fact that the tree dieback crisis caused the declining of oak in oak forest of Zagros. Oak decline is characterized by crown thinning, foliar necrosis and progressive death of primary leaf-bearing branches and the emergence and subsequent decline of foliage. A range of biotic and abiotic factors have been shown to contribute to the Oak decline. However, no satisfactory investigation has been established to explain the mistletoe distribution. Loranthus europaeus is mistletoe of significant management concern in The Zagros Forests, the west of Iran. Although most mistletoes do not affect their hosts seriously and may play a key role in the forest ecosystems, some species impact host fitness substantially. In cases where mistletoes require management, the implementation of successful control measures must take specific account of their ecology. Crown dieback is a manifest phenomenon that occurred in the Zagros oak forests during recent droughts. The impact of the presence of mistletoe on crown dieback has been proven. Since the effect of crown features on presence of mistletoe and crown dieback had been proven, it is necessary to investigate the relationship between the dieback and the characteristics of tree canopy of the trees with mistletoe. So investigating the spatial distribution of related parameters to dieback of trees in order to manage and control the mistletoe in The Zagros Forests and to prevent their damage to trees is important and must be done. 2- Materials and Methods In this study, the spatial distribution of tree dieback under the influence of mistletoe and tree features were investigated in Zagros Forest of Kermanshah (Gahvareh). Therefore, 86 plots (1600 m2) in a 200 m × 200 m sampling grid were established in Gahvareh Forests. In each one of the plots, the dieback and tree features including trees height, height of tree with mistletoes, crown diameter of tree with mistletoes, crown area, crown volume, crown dieback percentage and crown shape ratio the tree with mistletoe were recorded. Then the data were analyzed using geo-statistics (variogram) in order to describe and quantify the spatial continuity of variables. 3- Results and Discussion The results of the Pearson correlation coefficient indicate that dieback has a significant positive relationship with the tree properties including trees height, average of crown diameter, crown area and crown volume of trees with mistletoe. The variogram of variables revealed the presence of spatial autocorrelation for all variables. The variogram of variables were spherical and exponential. These variogram showed positive nugget, which can be explained by sampling error, short range variability, random and inherent variability. The nugget-to-sill ratio can be used to classify the spatial dependence of variables. The variable is considered to have a strong spatial dependence if the ratio is less than 25%, and has a moderate spatial dependence if the ratio is between 25% and 75%; otherwise, the variable has a weak spatial dependence. All variables were moderately spatially dependent except to crown volume of trees with mistletoe, which has a strong spatial dependency. The range of influence is considered as the distance beyond in which observations are not spatially dependent. The range of the variogram for tree height is: 4110 m, tree height with mistletoe: 4227m, average diameter of the tree crown: 4110 m, canopy diameter of tree with mistletoe: 4110 m, crown shape ratio of the tree with mistletoe: 5110 m, crown area of the tree with mistletoe is 2053 m and the percentage of crown dieback of trees with mistletoe is 4110 m. The range of height, tree height with mistletoe, average diameter of the crown tree, tree crown diameter with mistletoe and the percentage of crown dieback of trees with mistletoe are similar showing that these factors have a greater impact on the distribution of this variable. 4- Conclusion The studied variables occurred in a relatively large area, indicating the spatial structure of large, uniform distribution and continuity in the desired location in variable amounts. The similarity in the effect range of dieback and features of trees with mistletoe and also a significant positive correlation between them, represent a close spatial relationship between the dieback and trees features and the presence of mistletoe. These results can be used by the executive organs for the management of crown dieback caused by the presence of mistletoe in The Zagros Forests.